Marketing Strategy for Gold Pawn Products at BSI Teluk Kuantan Sub-Branch Office - Dwi Arsinta; Dian Meliza; Meri Yuliani; Santia Bella (Imara: Jurnal Riset Ekonomi Islam, 2025)
Background. The growth of the Islamic banking industry in Indonesia has driven the development of sharia-compliant financial products that provide alternatives to conventional interest-based financing. One such product is the gold pawn (rahn emas), which offers short-term financing secured by gold collateral and complies with Islamic principles. Purpose. This study aims to analyze the marketing strategy of the gold pawn product implemented by Bank Syariah Indonesia (BSI) KCP Teluk Kuantan. Additionally, it seeks to identify the supporting and inhibiting factors influencing the implementation of the marketing strategy in order to improve product competitiveness and sustainability. Method. This research uses a qualitative descriptive approach. The data were analyzed descriptively using the 7P marketing mix framework Results. The findings indicate that BSI KCP Teluk Kuantan has implemented a marketing strategy based on the 7P marketing mix, namely Product, Price, Place, Promotion, People, Process, and Physical Evidence. Supporting factors include strong market potential, growing public interest in sharia financial products, and internal support from the bank. Meanwhile, the main inhibiting factor is the limited number of employees, which affects service efficiency and marketing outreach. Conclusion. This study concludes that BSI KCP Teluk Kuantan has implemented the marketing strategy of the gold pawn (rahn emas) product based on the 7P marketing mix framework. This strategy supports the positioning of the product as a fast, secure, and sharia-compliant financing solution. The effectiveness of the strategy is supported by strong market potential and internal institutional support, while its main constraint lies in the limited number of employees, which affects service and marketing performance. These findings highlight the importance of optimizing human resources to improve the sustainability and effectiveness of sharia product marketing strategies..